Composite adaptive disturbance observer‐based control for a class of nonlinear systems with multisource disturbance. (24th April 2012) - Wei, Xinjiang; Chen, Nan; Li, Wuquan
SUMMARY Antidisturbance control and estimation problem are introduced for a class of nonlinear system subject to multisource disturbances. The uncertain multisource disturbances consist of not only a single harmonic or constant disturbance but also another unexpected nonlinear signal described as a nonlinear function. The composite adaptive disturbance observers are constructed separately from the controller design to estimate the disturbance with partial known information. By integrating disturbance observer‐based controller with robust adaptive control, a novel type of composite adaptive disturbance observer‐based control scheme is presented for a class of nonlinear system with multisource disturbances. Simulations for a flight control system are given to demonstrate the effectiveness of the results compared with the previous schemes. Copyright © 2012 John Wiley & Sons, Ltd.